Dastur Memorial Lecture Award* : Bio-diversity of Phytophthora species in India - R.S. MEHROTRA - MEHROTRA, R.S. (Indian Phytopathology, 2011)
Well, I have been asked to deliver the Dastur Memorial Lecture by Indian Phytopathological Society, New Delhi for which I express my gratefulness to the society. Before I actually talk with regard to biodiversity of Phytophthora species in India, I would like to pay my tribute to Late Professor Jahangir Fardunji Dastur (1886-1971). Dastur received world wide recognition on his monumental work in the discovery of a new species of Phytophthora and named by him as Phytophthora parasitica. Professor Dastur was an outstanding plant pathologist and was the first elected President of the Indian Phytopathological Society. In consonance of Professor Dastur’s immense contribution on Phytophthora parasitica responsible for blight of castor oil plants and foot rot and leaf rot of Piper betle L. caused by Phytophthora parasitica var. piperina, I have decided to talk about the bio-diversity of Phytophthora species in India. In all, around 34 species and varieties of Phytophthora have been reported from India so far (Table 1). The genus Phytophthora (Gr. Phyton, a plant, phthora, destroyer) was established by deBary (1876) with P. infestans de Bary as the type species. He recognized that the fungus causing late blight of potato in Europe in 1840’s previously identified as Botrytis infestans Montagne, later Peronospora infestans (Mont.) Caspary, had unique characteristics like branching of the sporangiophore (at first monopodial, secondary branches sympodial), the shedding of the sporangia, the formation of zoospores in the sporangium and the germination of the sporangium by zoospores or by tube, which he considered distinct enough to be assigned a new genus name. The genus Phytophthora contains a wide range of species, from primitive to advanced, from soil to soil-aerial habitats. Because of its economic importance, the taxonomy, biology and pathology of Phytophthora species has been extensively studied and reviewed by several workers.